The Vα14 invariant natural killer T cell TCR forces microbial glycolipids and CD1d into a conserved binding mode - Li, Yali (The Rockefeller University Press, 2010)
Invariant natural killer T cells (iNKT cells) rapidly produce effector cytokines. In this study, we report the first crystal structures of the iNKT cell T cell receptor (TCR) bound to two natural, microbial glycolipids presented by CD1d. Binding of the TCR induced CDR3-α–dependent structural changes in the F′ roof of CD1d; these changes resemble those occurring in the absence of TCR engagement when the highly potent synthetic antigen α-galactosylceramide (α-GalCer) binds CD1d. Furthermore, in the Borrelia burgdorferi α–galactosyl diacylglycerol–CD1d complex, TCR binding caused a marked repositioning of the galactose sugar into an orientation that closely resembles α-GalCer. The TCR-dependent reorientation of the sugar, together with the induced CD1d fit, may explain the weaker potency of the microbial antigens compared with α-GalCer. We propose that the TCR of iNKT cells binds with a conserved footprint onto CD1d, regardless of the bound glycolipid antigen, and that for microbial antigens this unique binding mode requires TCR-initiated conformational changes.